ANALISIS KASUS PRITA MULYASARI DALAM PUTUSAN PENINJIAUAN KEMBALI NO. 225 PK/PID.SUS/2011 - Nerissa Arviana; Sari Mandiana; Jusup Jacobus Setyabudhi (Universitas Merdeka Madiun, 2020)
Social media are growing so rapidly now, besides having a positive impact on society, it also has negative impacts such as hoaxes, pornography, and defamation. Some cases that are closely related to social media are criminal defamation in violation of the Information and Electronic Transactions Law, as experienced by Prita Mulyasari, a case that was initiated by sending a complaint email for Omni Hospital to her friends, so She was charged violating No. 11 of Information and Electronic Transactions Law year 2008, in this study the author uses the Doctrinal or Normative Juridical research methodology by discussing court decision No. 225 PK / PID. SUS / 2011 where in this case Prita Mulyasari was dismissed by the Tangerang District Court, but was found guilty at the Supreme Court level and finally was released free at the Judicial Review level.Keywords: Prita Mulyasari; RS. Omni; Information and Electronic Transaction Law